Implementation of Project Based Learning (PjBL) Electrochemistry Concepts - Amarlita, Dhamas Mega; Ningsih, Endang Utami (Journal of Evidence-Based Community Health, 2024)
Vocational high schools aim to form graduates who are ready to enter the world of work, be employed, or as entrepreneurs. To realize this goals, graduates must be equipped with relevant skills so that they are ready to compete in the world of work. One of them is by implementing the PjBL learning model. This service aims to improve electrochemical learning at SMK Islam 1 Blitar and improve teacher competence in designing learning with the PjBL method, as well as providing a fun experience for students. After the implementation, it can be seen that PjBL learning makes teacher more creative and innovative in compiling and designing learning.